Konteks, Referensi, dan Makna: Kajian Semantik - J. Sutomo . (Dinamika Bahasa dan Budaya, 2015)
In the study of linguistics, semantics is a branch of linguistics that studies of the meaning.Context, reference, and meaning are important parts of semantics.Context relates to the situation where the things and events take place that can help us understand the meaning. Referent is an activity that we do to convey or obtain information, through oral or written speech, or vision in the form of an image or symbol.Reference relates to the concept in our brain about the referent that we hear or see. There are many kinds of meaning, but conceptual meaning and associative meaning are more dominant than the others as they represent the two main sides of the meaning of an utterance. Key words:context, referent, reference, meaning.